Time to pregnancy among the wives of men exposed to organic solvents. Issue 1 (January 1998) - Sallmén, M; Lindbohm, M L; Anttila, A; Kyyrönen, P; Taskinen, H; Nykyri, E; Hemminki, K
Abstract : OBJECTIVES: To assess whether paternal exposure to organic solvents is associated with decreased fertility. METHODS: A retrospective time to pregnancy study was conducted among men biologically monitored for organic solvents. The workers were classified into exposure categories on the basis of work description and the use of solvents as reported in the questionnaires, and on biological exposure measurements. The relative fecundability density ratios (FDR--an analogue of incidence density ratio of clinically recognised pregnancies) were calculated with discrete proportional hazards regression. RESULTS: After three mailings 316 (72.1%) wives of the monitored men participated. The final study population consisted of 282 couples who did not use contraception at the beginning of pregnancy. The FDRs, adjusted for potential confounders, were 0.80 (95% confidence interval (95% CI) 0.57 to 1.11) and 0.74 (95% CI 0.51 to 1.06) for high or frequent and low or intermediate exposure, respectively. High or frequent and low or intermediate exposure were related to decreased fecundability among primigravida (FDRs 0.36; 95% CI 0.19 to 0.66 and 0.53; 95% CI 0.27 to 1.04) but not among couples with at least one previous pregnancy (FDRs 0.96; 95% CI 0.62 to 1.49 and 0.77; 95% CI 0.47 to 1.24). CONCLUSIONS: The findings of the study provide limited support for the hypothesis that paternal exposure to organic solvents might be associated with decreased fertility. Further studies with careful design are warranted.